2003
DOI: 10.1002/bip.10535
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan as a probe for acid–base equilibria in peptides

Abstract: We present results of time resolved fluorescence measurements performed in Tryptophan (Trp) derivatives and Trp-containing peptides in the pH range 3.0-11.0. For each compound a set of decay profiles measured in a given range of pH values was examined as a whole, using the global analysis technique. The data were fitted to two or three lifetime components and the analysis allowed the monitoring of the changes in the concentration of the different species contributing to the total fluorescence in that pH interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…The gas phase studies on ionic amino acids and proteins done so far, have dealt with protonated cations or metal ion complexes . The protonated, gas phase tryptophan has a shorter lifetime than neutral form and pH dependent studies of tryptophan fluorescence in solution shows the same trend with decreasing pH as the protonated form of the amino acid is favored . The hydration of protonated aromatic amino acids show that the ammonium group is able to host up to three water molecules and the carboxyl group one water molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas phase studies on ionic amino acids and proteins done so far, have dealt with protonated cations or metal ion complexes . The protonated, gas phase tryptophan has a shorter lifetime than neutral form and pH dependent studies of tryptophan fluorescence in solution shows the same trend with decreasing pH as the protonated form of the amino acid is favored . The hydration of protonated aromatic amino acids show that the ammonium group is able to host up to three water molecules and the carboxyl group one water molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] The protonated, gas phase tryptophan has a shorter lifetime than neutral form and pH dependent studies of tryptophan fluorescence in solution shows the same trend with decreasing pH as the protonated form of the amino acid is favored. [18] The hydration of protonated aromatic amino acids show that the ammonium group is able to host up to three water molecules and the carboxyl group one water molecule. High intrinsic hydrophilicity, charge-dipole, dipole-dipole interactions among water molecules and the lack of alternative fully exposed hydration sites are shown to be responsible for the higher water affinity of carboxyl group than ammonium group.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical calculations [31] indicated that in g − rotamers of Trp the intramolecular electron transfer process competes with fluorescence as a deactivation route for the excited state while in the g + rotamer the electron transfer rate predominates over the fluorescence. It was shown that in Trp there is a pH dependent interconversion between long and intermediate lifetimes reflecting interconversion between g − and trans rotamers [32], and in melanocyte stimulating hormone the changes in parameters of fluorescence decay came from the conformational changes driven by modifications in the ionization stated of titratable residues in the peptides [33].…”
Section: Fluorescence In Microheterogeneous Systemsmentioning
confidence: 99%
“…Carbonyl compounds can quench indol fluorescence, due to the formation of an excited state charge transfer complex between indole and a carbonyl group12; recent calculations by Callis and Vivian put in evidence the importance of a Trp ring‐to‐amide backbone charge transfer state as a promoter of quenching of the indole emission 15. The changes in the pH of the medium may also influence the Trp decay in proteins and peptides, and it was recently shown that Trp is an useful fluorescent probe to study acid–base equilibria of Trp derivatives and Trp‐containing peptides, applying the global analysis technique to a set of decay profiles measured in several pH values 16. The pH changes affect the decay by modifications in the rates of nonradiative decay processes competing with fluorescence either through direct interaction of titratable residues with the indol ring or by modifications in the local environment affecting the mechanisms of excited state deactivation.…”
Section: Introductionmentioning
confidence: 99%
“…As the peptides contain several titratable residues, a complex pattern of decays could be present in that range of pH values. We analyzed the heterogeneous fluorescence decay profiles using the global analysis technique,17 as applied by Marquezin et al16 in the study of Trp‐containing derivatives. The experimental decay profiles could be well fitted to a three‐exponential decay function and the pH‐dependent modifications in the preexponential factors were correlated to the occurrence of different peptide conformations associated with different Trp rotamers.…”
Section: Introductionmentioning
confidence: 99%